Genome sequence diversity of SARS-CoV-2 in Serbia: insights gained from a 3-year pandemic study - Novkovic, Mirjana; Banovic Djeri, Bojana; Ristivojevic, Bojan; Knezevic, Aleksandra; Jankovic, Marko; Tanasic, Vanja; Radojicic, Verica; Keckarevic, Dusan; Vidanovic, Dejan; Tesovic, Bojana; Skakic, Anita; Tolinacki, Maja; et al. (Frontiers in Microbiology, 2024)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the COVID-19 pandemic, has been evolving rapidly causing emergence of new variants and health uncertainties. Monitoring the evolution of the virus was of the utmost importance for public health interventions and the development of national and global mitigation strategies. Here, we report national data on the emergence of new variants, their distribution, and dynamics in a three-year study conducted from March 2020 to the end of January 2023 in the Republic of Serbia. Nasopharyngeal and oropharyngeal swabs from 2,398 COVID-19-positive patients were collected and sequenced using three next generation technologies: Oxford Nanopore, Ion Torrent and DNBSeq. In the subset of 2,107 SARS-CoV-2 sequences which met the quality requirements, detection of mutations, assignment to SARS-CoV-2 lineages and phylogenetic analysis were performed. During the three-year period we detected three variants of concern – Alpha(5.6%), Delta(7.4%) and Omicron(70.3%) and one variant of interest - Omicron recombinant “Kraken”(XBB1.5) (<1%), whereas 16.8% of the samples belonged to other SARS-CoV-2 (sub)lineages. The detected SARS-CoV-2 (sub)lineages resulted in eight COVID-19 pandemic waves in Serbia, which correspond to the pandemic waves reported in Europe and the USA. Wave dynamics in Serbia showed the most resemblance with the profile of pandemic waves in southern Europe, consistent with the southeastern European location of Serbia. The samples were assigned to sixteen SARS-CoV-2 Nextstrain clades: 20A, 20B, 20C, 20D, 20E, 20G, 20I, 21J, 21K, 21L, 22A, 22B, 22C, 22D, 22E, 22F, and six different Omicron recombinants (XZ, XAZ, XAS, XBB, XBF, and XBK). The ten most common mutations detected in the coding and untranslated regions of the SARS-CoV-2 genomes included four mutations affecting the spike protein (S:D614G, S:T478K, S:P681H, S:S477N) and one mutation at each of the following positions: 5'-untranslated region (5'UTR:241); N protein (N:RG203KR); NSP3 protein (NSP3:F106F); NSP4 protein (NSP4:T492I); NSP6 protein (NSP6: S106/G107/F108-triple deletion) and NSP12b protein (NSP12b:P314L). This national-level study is the most comprehensive in terms of sequencing and genomic surveillance of SARS-CoV-2 during the pandemic in Serbia and highlights the importance of establishing and maintaining good national practice for monitoring of SARS-CoV-2 and other virus circulating worldwide.